2022
DOI: 10.21608/esugj.2022.155979.1017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cellulases Production by Aspergillus niger Using Response Surface Methodology

Abstract: The recent developments in bioconversion of agricultural and industrial wastes to chemical feedstock led to extensive studies on cellulolytic enzymes produced by fungi and bacteria. Aspergillus niger is well known for its ability to produce cellulases. This study aimed to produce cellulolytic enzymes from A. niger. Thirteen isolates of Aspergillus niger were screened for cellulases production. A. niger 270 was the best one which formed the highest inhibition zone (9cm) with hydrolysis capacity of 1.32. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…A. niger plays a crucial role in the fermentation of S. alba by producing enzymes such as cellulase, which can degrade plant cell walls (Zohri et al 2022). This enzymatic activity breaks down components of organic matter that are difficult to digest into substrates more easily accessed and utilized by rumen microbes.…”
Section: Organic Matter Digestibilitymentioning
confidence: 99%
“…A. niger plays a crucial role in the fermentation of S. alba by producing enzymes such as cellulase, which can degrade plant cell walls (Zohri et al 2022). This enzymatic activity breaks down components of organic matter that are difficult to digest into substrates more easily accessed and utilized by rumen microbes.…”
Section: Organic Matter Digestibilitymentioning
confidence: 99%
“…The lignocellulolytic index on table 2 demonstrated that KB2 and KB3 isolate had moderate potentials as a lignocellulolytic hydrolyzing isolate (clear zones of 29.3 mm and 49.3 mm) while the cellulolytic indexes are 1.19 and 1.57 respectively. A study on the cellulase production of various isolates of Aspergillus niger also resulted in cellulolytic indexes (hydrolysis capacity/HC) ranging from 1.11 to 1.32 (Zohri et al, 2023). Various studies indicated that the majority of Aspergillus, Fusarium, Alternaria, Rhizopus, Penicillum and Trichoderma isolates were found to possess cellulolytic activity (Vieto et al, 2021;Vasiliauskienė et al, 2023;Pacheco et al, 2023).…”
Section: Cellulolytic Activitymentioning
confidence: 99%